Electrochemically driven C–N bond formation from CO2 and ammonia at the triple-phase boundary. Issue 14 (4th March 2022) - Li, Junnan; Kornienko, Nikolay
Abstract : Electrocatalytic formation of C–N bonds was achieved through the electrolysis of CO2 and NH3 over Cu catalysts. A combined analytical and spectroscopic approach gave insights into the reaction mechanism leading to formamide and acetamide products. Abstract : Electrosynthetic techniques are gaining prominence across the fields of chemistry, engineering and energy science. However, most works within the direction of synthetic heterogeneous electrocatalysis focus on water electrolysis and CO2 reduction. In this work, we moved to expand the scope of small molecule electrosynthesis by developing a synthetic scheme which couples CO2 and NH3 at a gas–liquid–solid boundary to produce species with C–N bonds. Specifically, by bringing in CO2 from the gas phase and NH3 from the liquid phase together over solid copper catalysts, we have succeeded in forming formamide and acetamide products for the first time from these reactants. In a subsequent complementary step, we have combined electrochemical analysis and a newly developed operando spectroelectrochemical method, capable of probing the aforementioned gas–liquid–solid boundary, to extract an initial level of mechanistic analysis regarding the reaction pathways of these reactions and the current system's limitations. We believe that the development and understanding of this set of reaction pathways will play significant role in expanding the community's understanding of on-surface electrosynthetic reactions as well as push this set of inherently sustainable technologies towards widespread applicability.